The Language of Destructive Cults: : Keyness Analyses of Sermons - Palayon, Raymund T.; Todd, Richard Watson; Vungthong, Sompatu (Communication & Language at Work, 2020)
Destructive cults are the most notable damaging religious groups in society where leaders convince their followers to engage in destructive acts. Examples of such cults include Peoples Temple led by Jim Jones and Heaven’s Gate led by Marshall Applewhite who convinced their followers to commit mass suicide. Previous research into destructive cults has mainly focused on their social-psychological development. This research breaks new ground by examining the patterns of linguistic features in the sermons of destructive cults indicating the characteristics of their language using keyness analyses. The main data sets are the sermons of Jim Jones and the sermons of Marshall Applewhite in the period leading to mass suicide. As a benchmark, these sermons were compared to the sermons of Billy Graham and the sermons of Rick Warren, leaders of mainstream religious groups. The findings show that the language of destructive cults based on the sermons of the leaders upholds extreme non-religious ideologies that cannot be found in the sermons of mainstream religious groups. The styles of their language focus on othering, intensifying, elaborating, and negating with the aim of controlling their followers. The results may allow destructive cults to be identified before damaging events occur.